Chromatin Landscape During Skeletal Muscle Differentiation - Hernández-Hernández, Oscar; Ávila-Avilés, Rodolfo Daniel; Hernández-Hernández, J. Manuel (Frontiers in Genetics, 2020)
Cellular commitment and differentiation involve the coordinated activation of specific sets of genes and the repression of others, through the cooperation of specialized molecular mechanisms. In addition to the activity of specific transcription factors and chromatin modifying enzymes, the three-dimensional organization of genes and their regulatory elements are recognized to play a crucial role in transcriptional regulation on multiple cellular contexts. Long-range interactions allow communication between promoters and distant regulatory elements, as well as the physical association of coordinately regulated genes and their localization at functionally distinct subnuclear compartments. Despite the longstanding recognition of the existence and of the functional relevance of chromatin loops, the molecular mechanisms responsible for the establishment of chromatin contacts and their impact on gene expression have begun to be elucidated only recently. Tissue specific transcription factors are key mediators of cell fate specification with the ability to reprogram cell types into different ones. A classic example of such master transcription factors is the muscle specific factor MyoD, which belongs to the family of Myogenic Regulatory Factors (MRFs). At the molecular level, MRFs regulate cell fate determination and terminal differentiation of the myogenic lineage-committed cells in a multistep process that converts multipotent mesodermal cells into myotubes and, subsequently, muscle fibers. This developmental process commences with progenitor proliferation, continues with exit from the cell cycle, early differentiation, alignment and fusion of the mononucleated myoblasts into multinucleated myotubes to achieve terminal differentiation. Although the epigenetics of muscle regeneration has been extensively addressed and discussed over the recent years, the influence of higher-order chromatin organization in skeletal muscle regeneration is still gaining attention. In this review, we will focus on the incipient work that addresses 3D genome architecture and its influence in cell fate determination and differentiation to achieve skeletal myogenesis, taking MyoD as an example of tissue specific master transcription factor. We will further discuss the functional interplay between chromatin modifications, non-coding RNAs and chromatin modifiers in muscle differentiation and finally we will visit known alterations of genome organization mediated by chromosomal fusions giving rise to novel regulatory landscapes, enhancing oncogenic activation in muscle such as rhabdomyosarcomas.